PROSES PERBAIKAN DENGAN REWINDING PADA STATOR MOTOR AC ROTOR SANGKAR 3 FASA 380 V 400 KW 761 A DI PT. MESINDO TEKNINESIA CILINCING â JAKARTA UTARA - , RADHILIA SOFIANNA R ([Yogyakarta] : Universitas Gadjah Mada, 2014)
An induction motor is an alternating current electric motors which the most widely used. Called induction motor as the motor works by the induction of the magnetic field of the stator to the rotor, which the currents of rotor produced by induction that arise cause there is difference of relative between the field rotary rotation rotor produced by the currents of stator. In the industry, the induction motor is applicated as one of the drivers who used directly to support the production, so that it takes maximum care to maintain the effeciency of the induction motor. One of the factors that can affect the effeciency of an induction motor is winding or winding insulation damage to the motor. In this opportunity for the internship that the writer is working Final Project case study of a 3 phase induction motor squirrel cage rotor with a power output of 400 Kw, voltage input of 380 V and a frequency of 50 Hz, where ever there is damage on te stator. The repaire steps of induction motor are done by rewindng process. This process included change with full winding due to the winding has burned it. In the process of reparation there are many measurments by using a Electrical Apparatus Service Assocation (EASA).